Acupuncture treatment of diabetic peripheral neuropathy: an overview of systematic reviews based on evidence mapping - Jiang, Junjie; Shen, Hao; Zhang, Yi; Li, Yuanyuan; Jing, Yuanyuan; Chen, Xinyi; Wu, Hongli; Xie, Yanming; Liu, Huan (Frontiers in Neurology, 2024)
Objective The study attempted to evaluate the meta-analyses (MAs) of the acupuncture treatment of diabetic peripheral neuropathy (DPN) to provide a basis for clinical decision-making. Methods Eight databases, such as PubMed, Cochrane Library, Embase, Web of Science, CNKI, Wanfang Data, CQVIP, and CBM, were searched from database creation to December 22, 2023. The MAs of DPN treatment using acupuncture or acupuncture combined with conventional Western medicine were included. AMSTAR-2 and PRISMA 2020 helped evaluate the methodological and reporting quality of the included studies. The GRADE methodology helped assess the evidence quality of outcome indicators. Evidence mapping was performed to display evaluation results. Results A total of 18 MAs involving 23,240 DPN patients were included. Based on the methodological quality evaluation, four MAs were of “moderate” quality, seven had a quality grade of “low,” and another seven were of “critically low” quality. The evidence quality evaluation showed that among studies of acupuncture vs. conventional Western medicine, four had an evidence quality of “moderate,” 18 had an evidence quality of “low,” and 17 had an evidence quality of “critically low” and that among studies of acupuncture + conventional Western medicine vs. conventional Western medicine, 12 had an evidence quality of “moderate,” 29 had an evidence quality of “low,” and 33 had an evidence quality of “critically low.” Compared with conventional Western medicine, simple acupuncture and acupuncture + conventional Western medicine significantly improved total effective rate (TER) and nerve conduction velocity (NCV). Conclusion Acupuncture treatment of DPN significantly improves TER and NCV with proven safety. However, the MAs of the acupuncture treatment of DPN must strictly refer to relevant standards and specifications regarding methodological and reporting quality, along with the design, execution, and reporting of primary randomized controlled trials (RCTs).